A vector control of a grid-connected 3L-NPC-VSC with DFIG drives - Srirattanawichaiku W. (2014)
This paper presents a vector control of grid-connected three-level neutral point clamped voltage source converter (3L-NPC-VSC) connecting doubly-fed induction generator (DFIG) drives for variable-speed wind power generation. The control algorithm of the grid-connected 3L-NPC-VSC applies the concepts of the decoupled vector control method, which provides independent control active and reactive power flow and maintain the dc-link voltage constant. The simulation results are shown dynamic and steady-state performance of the grid-connected 3L-NPC-VSC in mode sub-synchronous and super-synchronous speed at low switching frequency that compared with a conventional two-level voltage source converter (2L-VSC). The control strategy is verified by the simulation results with a good sinusoidal current, a low harmonic component and a fast dynamic response.